Comparative analysis of skin color in breast reconstruction using pedicled transverse rectus abdominis myocutaneous flaps - Kim, Woo Hyeong; Choi, Jun Ho; Kim, Kwang Seog; Lee, Sam Yong; Hwang, Jae Ha (Archives of Aesthetic Plastic Surgery, 2022)
Background A recent concern in breast reconstruction procedures is skin color mismatch of the pedicled transverse rectus abdominis myocutaneous (TRAM) flap. With the goal of objectively quantifying the skin tone of the TRAM flap donor site, contralateral breast, and flap, a comparative study was conducted.Methods This study was conducted in July 2021, included 17 patients who received delayed breast reconstruction via TRAM flaps from January 2016 to December 2020 with at least 12 months of follow-up. Melanin levels and redness values of the flap, abdomen, and contralateral breast were measured in patients using a skin pigmentation analyzer. Furthermore, in 20 healthy women in their 40s to 60s, measurements were made of the abdomen, as well as breast.Results The contralateral breast had lower mean melanin and redness than the abdomen. The flaps had slightly higher melanin levels than the contralateral breasts. The flaps tended to have higher redness values, but the difference was not significant. The difference between the flap and abdomen was significant for melanin, but not redness. Preoperative radiotherapy did not affect skin tone. The upper abdomen showed lower melanin and redness than the lower abdomen.Conclusions The breast had a brighter skin tone than the abdomen. The upper abdomen showed brighter skin tone than the lower abdomen, and the area used as the donor site of the TRAM flap presented the same tendency. In the process of TRAM flap engrafting, the melanin level of the tissue decreases, and the redness value tends to increase slightly compared to the contralateral breast.